1990
DOI: 10.1007/bf01868460
|View full text |Cite
|
Sign up to set email alerts
|

Zinc inhibition of chloride efflux from skeletal muscle ofRana pipiens and its modification by external pH and chloride activity

Abstract: Efflux of 36Cl- from frog sartorius muscles equilibrated in depolarizing solutions was measured. Cl- efflux consists of a component present at low pH and a pH-dependent component which increases as external pH increases. In depolarized muscles from Rana pipiens, the pH-dependent Cl- efflux has an apparent pKa near 6.4. The reduction of Cl- efflux by external Zn2+ was determined at different external pHs and chloride activities. The effect of external chloride activity on the pH-dependent Cl- efflux was also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Lowering pH o decreases the effectiveness of ZnCl 2 . Competition between Zn 2+ and H + has been noted previously for other channels, including Cl − (Hutter and Warner 1967; Spalding et al 1990; Rychkov et al 1997) and K + (Spires and Begenisich 1992, Spires and Begenisich 1994). We consider whether the pH o dependence indicates that (a) the active form is not Zn 2+ but ZnOH + , (b) Zn 2+ and H + compete for the same binding site, or (c) there is noncompetitive inhibition; i.e., protonated channels have a lower affinity for Zn 2+ .…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Lowering pH o decreases the effectiveness of ZnCl 2 . Competition between Zn 2+ and H + has been noted previously for other channels, including Cl − (Hutter and Warner 1967; Spalding et al 1990; Rychkov et al 1997) and K + (Spires and Begenisich 1992, Spires and Begenisich 1994). We consider whether the pH o dependence indicates that (a) the active form is not Zn 2+ but ZnOH + , (b) Zn 2+ and H + compete for the same binding site, or (c) there is noncompetitive inhibition; i.e., protonated channels have a lower affinity for Zn 2+ .…”
Section: Introductionsupporting
confidence: 64%
“…The absolute concentration of ZnOH + is a small fraction of the total, and >90% of ZnCl 2 is divalent at pH < 8.0, hence [Zn 2+ ] remains relatively constant (Baes and Mesmer 1976). Spalding et al 1990 concluded that ZnOH + was the active form for Cl − currents in muscle. The “consensus” potency sequence for inhibiting H + currents by divalent metal cations, Cu < Zn > Ni > Cd > Co > Mn > Ba, Ca, Mg < 0 (DeCoursey 1998), is intriguingly similar to the tendency of these cations to hydrolyze (Perrin and Dempsey 1974) (indicated by their pK a ): Cu (8.0) > Co (8.9), Zn (9.0) > Ni, Cd (9.9) > Mn (10.6) > Mg (11.4) > Ca (12.6) > Ba (13.4).…”
Section: Discussionmentioning
confidence: 99%
“…10), thus confirming this recent finding. Skeletal muscle chloride channels are known to be blocked by external zinc (Spalding, Taber, Swift & Horowicz, 1990;Hille, 1992), and this effect is reported to be voltage independent (Woll, Leibowitz, Neumcke & Hille, 1987). In the case of the swelling-activated chloride channel, it is possible that divalent metals also act externally, in such a voltageinsensitive manner, to 'facilitate' an inherent voltagedependent inactivation process of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Cations can block membrane Cl-channels. Zn2+ has long been known to inhibit Cl-efflux from skeletal muscle relaxation over the duration of the voltage clamp pulse (Stanfield, 1970;Spalding et al 1990), as do H+ ions (Spalding et al 1990;Ackerman et al 1994), but other divalent cations, specifically Mg2+, seem to be without extracellular action (Spalding et al 1990 (Lauf, Erdmann & Adragna, 1994). Intracellular Mg2+ also regulated the appearance of cell-swelling-activated Cl-channels in neutrophils (Stoddard et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In other systems, other mechanisms for current decay include cation block and ion-dependent inactivation. Zinc ions have long been known to block Clchannels in skeletal muscle (Stanfield, 1970;Spalding, Taber, Swift & Horowicz, 1990), and the trivalent cations La3+ and Gd3+ also block cell-swelling-activated Clchannels (Ackerman, Wickman & Clapham, 1994). Mg2+ ions are well known to block a wide variety of cation channels.…”
mentioning
confidence: 99%